1975
DOI: 10.1271/bbb1961.39.1123
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa elastase: affinity chromatography and some properties as a metallo-neutral proteinase.

Abstract: Pseudomonas aeruginosa elastase was found to be a typical metallo-neutral proteinase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…Zinc (Zn) and calcium (Ca) ions have previously been shown to be required for enzyme activity and stability of elastase, respectively (21,22). Iron (Fe) (2) and, more recently, Zn (3) have also been implicated in the regulation of elastase production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc (Zn) and calcium (Ca) ions have previously been shown to be required for enzyme activity and stability of elastase, respectively (21,22). Iron (Fe) (2) and, more recently, Zn (3) have also been implicated in the regulation of elastase production.…”
Section: Resultsmentioning
confidence: 99%
“…Proelastase is then further processed to its mature 33-kDa form via autoproteolytic processing mechanisms. In this regard, McIver et al (20) have recently shown that substitutions at the active site residue His-223 resulted in both loss of proteolytic activity and accumulation of the unprocessed 51-kDa form of elastase when expressed in Escherichia coli (22).…”
mentioning
confidence: 99%
“…Many studies have been carried out on the mechanisms of the bacterial colonization and the pathogenesis of chronic infections in the lower respiratory tracts, and some cilio-inhibitory substances, produced by P. aeruginosa, St. pneumoniae, and H. influenzae have already been isolated [14][15][16][17][18]26]. It is well-known that P. aeruginosa, in particular, releases several cilio-inhibitory substances, such as phenazine pigments (pyocyanin, 1-hydroxyphenazine) [14,26], haemolysin (rhamonolipid) [15], and at least two kinds of proteinases (elastase, alkaline protease) [16,[27][28][29]. It is also known that human neutrophil elastase causes damage to the host tissues, including respiratory ciliated epithelium, as well as to pathogenic micro-organisms [16,23].…”
Section: Discussionmentioning
confidence: 99%
“…Heat denaturation, or formaldehyde inactivation of enzyme activity with preservation of immunogenicity, completely abolish mucin release activity of P. aeruginosa elastase. In addition, removal of Zn+2 from the assay system with phenanthroline under conditions of calcium sufficiency significantly diminished the activity of this metalloproteinase (38). This approach was required because the simple addition of EDTA or other chelators of divalent cations alters the secretory response of tracheal epithelium (39).…”
Section: Discussionmentioning
confidence: 99%